VD_FINDINFO HC / 2012 / 517 vom 4. Juli 2012 - VD Tribunal cantonal (2012)
BAIL À LOYER, ANNULABILITÉ, RÉSILIATION, PROLONGATION DU BAIL À LOYER | 269d CO, 271a al. 1 let. d CO, 271a al. 1 let. e CO, 272b al. 1 CO, 272b CO